Adult Congenital Heart Disease in Clinical Practice (In Clinical Practice,, 2018)
There is an evident practice gap in education of general adult cardiologists on long-term management of congenital heart disease (CHD). The goal of this book is to help general cardiologists, but also pediatricians and related care providers in the management and diagnosis of adult CHD. Adult Congenital Heart Disease in Clinical Practice provides clear, practical advice on adult CHD for the busy fellow, resident and practicing clinician. It includes training and revision material to assist learning and is formatted in such a way as to provide short, concise content designed for easy recall of salient facts.